2020
DOI: 10.1029/2020wr027755
|View full text |Cite
|
Sign up to set email alerts
|

Drought Propagation in Contiguous U.S. Watersheds: A Process‐Based Understanding of the Role of Climate and Watershed Properties

Abstract: Drought impacts on the society and environment are influenced by how droughts propagate through the hydrologic cycle; however, the physical processes involved in drought propagation are not well understood. In this study, a physically based hydrologic model is used to understand the drought propagation mechanisms and their controlling factors in multiple watersheds selected from different regions of the contiguous United States (CONUS). The characteristics of hydrologic droughts are found to be significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 83 publications
4
38
1
Order By: Relevance
“…(2019) analyzed the relationship between socioeconomic drought and meteorological drought in the Datong River Basin and found that El‐Niño Southern Oscillation (ENSO) had the greatest impact on drought propagation among several climate indices. However, global studies have found that there are various factors that can affect the drought propagation, including watershed properties, climate types and human activities (Apurv & Cai, 2020; Gevaert et al., 2018; J. F. Wu et al., 2017). Therefore, drought propagation usually has regional characteristics (N. C. Chen et al., 2020; R. H. Li, Chen, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2019) analyzed the relationship between socioeconomic drought and meteorological drought in the Datong River Basin and found that El‐Niño Southern Oscillation (ENSO) had the greatest impact on drought propagation among several climate indices. However, global studies have found that there are various factors that can affect the drought propagation, including watershed properties, climate types and human activities (Apurv & Cai, 2020; Gevaert et al., 2018; J. F. Wu et al., 2017). Therefore, drought propagation usually has regional characteristics (N. C. Chen et al., 2020; R. H. Li, Chen, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The renewable water supply deficits during droughts are the highest in the Central US, followed by the Western US, and the lowest in the Eastern US watersheds. The renewable water supply deficits are the largest in the Great Plains region due to large water demands relative to the renewable water availability (Apurv & Cai, 2020), a major fraction of which is fulfilled from the unsustainable use of the deep groundwater from the High Plains aquifer (Scanlon et al., 2012). There is a stark contrast between the water supply drought characteristics in the Western and Eastern US watersheds.…”
Section: Resultsmentioning
confidence: 99%
“…where N is the number of water supply drought events, WSD i is the water supply deficit during the ith drought event and WD is the annual water demand in the year 2015 (Apurv & Cai, 2020). Figure 2 shows the results of the analysis of the multidecadal variability of meteorological droughts using the moving-window approach.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations